7PS MARKETING MIX AND RETAIL BANK CUSTOMER SATISFACTION IN NORTHEAST NIGERIA - Isa Mohammad, Haruna (British Journal of Marketing Studies, 2015)
Customer satisfaction is a continuous process that management must engage in. This study analysed customer satisfaction using 7Ps marketing mix elements to retail bank customers in North east Nigeria. Objectives include examining product, price, place, promotion people, process and physical evidence as drivers of retail bank customer satisfaction. Seven hypotheses were formulated to address the objectives. Data were collected from a sample size of 405 respondents comprising of academic and senior non-academic staff in universities and polytechnics in North east region of Nigeria through questionnaire administration. The study used correlation and regression analysis. The results found that product, process and physical evidence were significantly related to customer satisfaction while price, promotion, place and people are not significantly related. It was also found that process is the most influential driver while price is the least influential. Finally, the study recommends that management should improve the marketing mix elements by applying the right mix to attract and retain customers.